Effective treatment for vulvovaginal candidiasis: case reports - Tikhomirov A.L; Sarsaniya S.I (LCC «Medicine-Inform», 2019)
Effective treatment for vulvovaginal candidiasis: case reports A.L. Tikhomirov1, S.I. Sarsaniya2 1A.I. Evdokimov Moscow University of Medicine and Dentistry, Moscow, Russian Federation 2LLC "S-Mariya", Moscow, Russian Federation Treatment resistance remains a concern for gynecologists who face with vulvovaginal candidiasis. The signatures of Candida colpitis are high morbidity, long-term course, frequent recurrences, potential generalization with the involvement of other organs and systems, high resistance to antifungal agents, and challenges in treatment during pregnancy. Topical antifungal therapy is first-line option for vulvovaginal candidiasis due to its local effect in the immediate nidus of infection and rapid symptom relief (within few days of starting treatment). Adverse reactions are among the most common reasons to refuse treatment. In addition, subjective tolerability of adverse reactions and easy use are important since these factors improve treatment adherence and provide treatment success. Effective and appropriate antifungal agent should be administered. Natamycin, safe polyene antimycotic, meets these requirements. The paper reviews clinical cases illustrating treatment efficacy of vulvovaginal candidiasis with natamycin. Keywords: vulvovaginal candidiasis, antifungal resistance, fungicidal effect, safety, natamycin. For citation: Tikhomirov A.L., Sarsaniya S.I. Effective treatment for vulvovaginal candidiasis: case reports. Russian Journal of Woman and Child Health. 2019;2(2):155-159.